LEARNING SEQUENCES USING MATHEMATICAL MODELLING - Permata, Endah Dwi; Zulkardi, Zulkardi; Darmawijoyo, Darmawijoyo (Sriwijaya University Learning and Education International Conference, 2018)
The main principle in today's mathematics learning was to improve and prepare learning activities that gave benefit to students who aim to move from teaching mathematics to learning mathematics and the solution was translate again as a real-world problem solution. This study aims to generate learning path that used mathematical modeling so that it can help students understand the material sequence. The research method used design research. Hypotetical Learning Trajectory in design research played an important role as design and research instrument. HLT was designed in the initial design phase and tested in grade IX students (ie, 6 students on pilot experiment and 35 students in teaching experiment) SMA Negeri 4 Pagaralam. In retrosvectife analysis, actual learning during teaching experiments compared with HLT has been designed to show that with the context of the model of business development and using mathematical modeling can help students in understanding the learning sequence.